Molecular epidemiology and phylogenetic insights of lumpy skin disease in cattle from diverse agro-ecological regions of Punjab, Pakistan - Muhammad Haider Jabbar; Farhan Ahmad Atif; Muhammad Kashif; Ishtiaq Ahmed; Fabrizio Iarussi; Ayman A. Swelum (PLoS ONE, 2025)
Lumpy skin disease (LSD) is an emerging, highly contagious transboundary disease of bovines caused by the Lumpy skin disease virus (LSDV), responsible for substantial economic losses to the dairy, meat, and leather industries in Pakistan as well as various countries around the world. Epidemiological information on LSD is scarce in Punjab, Pakistan. Therefore, a molecular epidemiological study was conducted in two agro-ecologically diverse districts (Bhakkar and Jhang) of Punjab, Pakistan. A total of 800 blood samples were randomly collected from the jugular vein of clinically suspected cattle with nodular lesions using a multistage cluster sampling technique. The sampling unit was indigenous, crossbred, and exotic breeds of cattle. Four hundred samples were collected from each district. Ten union councils (UC) were selected from each district, and two villages were selected from each union council. From each village, twenty cattle were selected for sample collection. The PCR-based overall prevalence of LSDV in clinically suspected cattle using the P32 gene was 36.25% (36.25%; 290/800). The multivariable logistic regression analysis indicated that animals who were not treated with acaricide (P = 0.014; OR = 1.459; C.I = 1.079–1.972), body condition score (emaciated animals; P = 0.019; OR = 1.573; CI = 1.076–2.301), and gender (female; (P = 0.016; OR = 1.435; CI = 1.072–1.969) were significantly at higher risk for LSDV infection in cattle. The phylogenetic insights revealed that our isolates were linked to Kenya, China, Russia, Egypt, India, Zimbabwe, Iraq, and Iran. It can be concluded that LSD is widely distributed in the study area, with evidence of genetic diversity. Further studies are required on genetic composition using variable genetic markers for effective control and eradication of LSDV in Pakistan.